AN INTRODUCTOY REFLEXION ON POLEMOS IN HERACLITUS’ DK 53 - Luiz, Felipe [UNESP] (My University, 2020)
The thought of Heraclitus from Ephesus continues to interest us in spite of the millennia that apart us from it. The aim of this paper is to articulate some interpretative questions on terms of the fragment 53 DK, in which Heraclitus use the concept polemos, that is, war.
UMA REFLEXÃO INTRODUTÓRIA SOBRE O POLEMOS NO FR. 53 DK DE HERÁCLITO
Keywords: Ancient Philosophy; Heraclitus of Ephesus; ontology; polemos